Histopathological profile of cervical biopsy specimens at Paropakar Maternity and Women’s Hospital - Malla Vaidya, Karishma; Baral, Gehanath; Joshi, Bandana; Shrestha, Bigya (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: The lesions at uterine cervix cannot be always established only with cytology. Thus, it is very important that cytological abnormality be subsequently correlated with biopsy for confirmation of cervical lesion. Thus it is to see histopathological findings of different types of cervical pathology in cervical biopsies. Methods: This is retrospective analysis of histology result of 1184 cervical biopsy specimens from 2011 to 2016. Results: Out of 1108 histologically adequate cervical specimens, benign cervical lesion formed the major part (44.76%)followed by cervical inflammatory lesion (27.43 %). Malignant and borderline cervical lesion constituted 14.35% and 13.44% respectively; 6.4% biopsy samples were inadequate to report.CIN I was common among borderline lesions followed by CIN III. The most common cervical malignancy was squamous cell type and mostly moderately differentiated. Conclusions:Benign cervical lesions were the most common cervical lesions followed by inflammatory conditions. Among borderline cervical lesions CIN I was commonly found followed by CIN III.